ENVIRONMENTAL AND PHYSIOLOGICAL FACTORS AFFECTING IN VITRO BULBLET FORMATION OF EUCOMIS ZAMBESIACA - Cheesman, L.; Finnie, J.; Van Staden, J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Eucomis L Hér. is a genus of 11 species that fall within the Hyacinthaceae family. Eucomis species are used in southern African traditional medicine for the treatment of various ailments, in particular, pain and inflammation. Eucomis zambesiaca Baker is a related species to Eucomis autumnalis which is widely used in South Africa. It is a summer-blooming bulbous geophyte occurring from northern South Africa to Malawi. Micropropagation is a useful technique for rapid clonal multiplication of plant material which could potentially yield useful secondary metabolites as well as alleviate the pressure on the wild plant populations. Experiments were carried out to determine optimal growth conditions for bulblet production. Different carbohydrates such as fructose, sucrose and glucose were tested at concentrations of 3, 6, 9 and 12%. Plant growth regulators (GA3, IAA, IBA, NAA, BA, zeatin, iP and others) were tested at concentrations of 1, 2 and 5 mgL-1. Maximum number of bulblets per explant was obtained at 20°C, with an average of three bulbs per leaf explant. The average bulblet mass was 52 mg, which was significantly higher than bulblets formed at other tested temperatures. Explants at 25°C grew more rapidly but fewer bulblets formed. A protocol for mass bulblet production has been established and plants were successfully acclimatized.